1994
DOI: 10.1111/j.1600-0447.1994.tb01588.x
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic medication and suicide risk among schizophrenic and paranoid inpatients

Abstract: A retrospective analysis of the psychotrophic medication, illness history and recent mental symptoms of 28 schizophrenic or paranoid inpatients who had committed suicide and the same number of matched control subjects was carried out. The groups were first compared separately for every variable, and 6 statistically most significant variables in the paired comparisons were then entered into a stepwise linear logistic regression model. Four statistically significant differences between the groups were found with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 26 publications
2
18
0
4
Order By: Relevance
“…Our findings, therefore, reflect an association between predominant illness symptom type over a 9-month period and long-term suicide risk. It is important to note that symptoms and other potentially relevant factors proximate to the actual suicidal events were not recorded in this study but have been described in studies of other patients as heterogeneous (11,13,39).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings, therefore, reflect an association between predominant illness symptom type over a 9-month period and long-term suicide risk. It is important to note that symptoms and other potentially relevant factors proximate to the actual suicidal events were not recorded in this study but have been described in studies of other patients as heterogeneous (11,13,39).…”
Section: Discussionmentioning
confidence: 99%
“…Personality traits such as aggression and impulsivity have been associated with suicidal behavior in psychiatric patients when ratings of the objective severity of the depression or psychosis have also been taken into account [27]. In patients with schizophrenia, an association between impulsivity, but not with aggression, and suicidal behavior has been reported [56,87]. Other social factors, such as living alone or not living with one's family, and the experience of a recent loss, have been associated with an increased risk of suicide, indicating the importance of social support; subsequent living with one's family might be a protective factor against suicide.…”
Section: Reviewmentioning
confidence: 99%
“…These findings fail to support the hypothesis that antipsychotics induce suicide attempts, but the findings also do not prove benefit; the medication differences between suicidal and nonsuicidal patients likely reflect differences in illness severity rather than a direct beneficial effect of the neuroleptic. In fact, Taiminen and Kujari 90 suggest that the suicidal patients may have received lower neuroleptic doses because they displayed significantly more depressive and fewer positive symptoms than controls. Depressive symptoms often do not respond to conventional antipsychotics.…”
Section: Conventional Antipsychoticsmentioning
confidence: 98%
“…In mostly retrospective studies of schizophrenic suicide victims compared to matched controls, authors have reported significantly lower [89][90][91] or similar 92,93 neuroleptic doses in the suicide group compared to controls. In a study by Wilkinson and Bacon, 94 there was no difference in antipsychotic use between schizophrenics who completed suicide and controls who were matched for age and sex.…”
Section: Conventional Antipsychoticsmentioning
confidence: 99%